2022
DOI: 10.4018/ijcac.297103
|View full text |Cite
|
Sign up to set email alerts
|

Device Access Control and Key Exchange (DACK) Protocol for Internet of Things

Abstract: Internet of Things is a promising technology but it also increases numerous security threats in data transmission. To secure neighboring sensing devices' communication in an IoT environment, a key agreement protocol is primordial. Various IoT data transmission mechanisms have been proposed in the literature to attain security. However, these propositions are not completely secure against all types of attacks. In this paper, a new certificate-based was proposed lightweight authentication and key agreement proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The paper suggested a new methodology that reduces the number of operations required to produce secret keys by utilizing elliptic curve cryptography [54]. The next step has been the presentation of research difficulties and future directions for further developing the suggested system [55,56].…”
Section: Blockchain Technologymentioning
confidence: 99%
“…The paper suggested a new methodology that reduces the number of operations required to produce secret keys by utilizing elliptic curve cryptography [54]. The next step has been the presentation of research difficulties and future directions for further developing the suggested system [55,56].…”
Section: Blockchain Technologymentioning
confidence: 99%
“…It is predicted that 4G may arrive at the bottleneck before 2020, and 5G might be 2030. However, the upcoming wireless network system is being evolved based on recent advances in wireless and networking systems such as software-defined networking and virtualization in 5G and Artificial Intelligence (AI), Internet of Thing (IoT), Internet of Everything (IoE) and Virtual Reality need high reliability, low latency and ultra-high-speed for the uploading and downloading in 6G (Ahmad & Afzal, 2020) (Almrezeq et al, 2022). 5G has higher bit rates with more than 10 gigabits per second than previous technologies, more capacity, and low latency.…”
Section: Introductionmentioning
confidence: 99%